Estimating sedimentary thickness of Lanka Basin using digitised scanned seismic sections - Silva, K.C.C.; Gamage, N.G.S. S.; Weerasinghe, D.A. (My University, 2019)
In exploration geophysics, seismic surveys and their interpretations provide the most reliable information of the subsurface structures. Extensive work on the determination of the subsurface structure has been carried out in both 􀀦􀁄􀁘􀁙􀁈􀁕􀁜􀀃 􀁄􀁑􀁇􀀃 􀀰􀁄􀁑􀁑􀁄􀁕􀀃 􀁅􀁄􀁖􀁌􀁑􀁖􀀃 􀁒􀁉􀀃 􀁒􀵵􀁖􀁋􀁒􀁕􀁈􀀃 􀀶􀁕􀁌􀀃 􀀯􀁄􀁑􀁎􀁄􀀑􀀃 􀀩􀁕􀁈􀁈􀁏􀁜􀀃 available satellite- gravity and magnetic data suggest that the Lanka Basin may have the necessary sediment volume for the occurrence of hydrocarbons. However, without seismic data, this suggestion cannot be tested further. As an alternative to acquiring additional seismic data in the region, this research focused on digitising 50,000 km of vintage seismic lines from the National Geophysical Data Centre (NGDC) data repository and converting them into Seg-Y format. Key seismic horizons on the digitised sections were interpreted to provide details of the seabed and acoustic basement in the time domain. Regional sedimentary thickness maps were compiled in the time domain interpolating the interpreted horizons using ‘􀁎􀁕􀁌􀁊􀁌􀁑􀁊’ method. The velocity data acquired in the region were used to convert the maps from time to depth domain. The results indicate that average thickness of sediments in the region varies around 5000 m to 6000 m, where the maximum thickness is around 8000 m in the North Eastern part of the Lanka basin. The thickness maps can be used as a reference dataset to plan commercial seismic surveys in the future for hydrocarbon exploration in the Lanka Basin.
Keywords: Lanka basin, NGDC, passive margins, seismic surveys, thickness model.